2022
DOI: 10.2991/assehr.k.220203.025
|View full text |Cite
|
Sign up to set email alerts
|

Students Diversity and the Implementation of Adaptive Learning and Assessment

Abstract: Identification of the diversity of students is often an important point that teachers rarely consider before the learning is carried out. In fact, by understanding this diversity, teachers can undoubtedly carry out adaptive learning and assessments that are suitable for the conditions of students. This study aims to identify the importance of knowing the diversity of students and how teachers can implement appropriate learning and assessment. A systematic literature study was used in this study. Researchers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The fidelity of the curriculum used in the academy is part of adaptive learning where the cadets can adapt to the learning method being implemented. This is in accordance with the statement that adaptive learning is adapted to context analysis, learning load analysis, academic unit analysis, and curriculum analysis (Ramdani et al, 2022). The racial differences in the cadets study give recommendations a highlight potential untapped resource for solving the labor shortage facing the entire aviation industry (Stevenson et al, 2020).…”
Section: Figure 4 Aptitude Test Comparisonsupporting
confidence: 77%
See 1 more Smart Citation
“…The fidelity of the curriculum used in the academy is part of adaptive learning where the cadets can adapt to the learning method being implemented. This is in accordance with the statement that adaptive learning is adapted to context analysis, learning load analysis, academic unit analysis, and curriculum analysis (Ramdani et al, 2022). The racial differences in the cadets study give recommendations a highlight potential untapped resource for solving the labor shortage facing the entire aviation industry (Stevenson et al, 2020).…”
Section: Figure 4 Aptitude Test Comparisonsupporting
confidence: 77%
“…Identification of the diversity of students is often an important point that teachers rarely consider before the learning is carried out. In fact, by understanding this diversity, teachers can undoubtedly carry out adaptive learning and assessments that are suitable for the conditions of students (Ramdani et al, 2022). Around 40% of the teachers repudiated the influence of diversity on student achievement and did not take student diversity into account in their teaching practice (van Middelkoop et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers proposed that embedded use of differentiated instruction with various teaching strategies could develop opportunities for students to maximize individual growth and success in learning (Gheyssens et al, 2020 ; Ismail & Allaq, 2019 ; Ramdani et al, 2021 ). Our study found that the individual learning style score significantly decreased but the group learning style score significantly increased at the end of the semester.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the challenge that students are more diversified in higher education due to their varied educational and life experiences (Trolian & Parker III, 2022 ). Because of the diversified characteristics, students demonstrate varying learning abilities, learning styles and academic levels in classrooms (Ramdani et al, 2021 ). Tomlinson ( 2001 ) asserts that students learn best when their teachers accommodate the differences in their readiness levels, interests and learning profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Peserta didik dengan minat tinggi pada sejarah menunjukkan peningkatan keterlibatan dan retensi informasi yang dipelajari (Latief et al, 2023). Selain itu, Keragaman kemampuan peserta didik memiliki pengaruh yang signifikan terhadap proses belajar (Gronseth et al, 2021;Ramdani et al, 2022). Penting bagi pendidik untuk mengenali berbagai preferensi belajar, kemampuan, dan pengalaman yang dimiliki oleh peserta didik ketika mereka memasuki sekolah.…”
Section: Pendahuluanunclassified